OPTICAL BISTABILITY IN A DEGENERATE TWO-LEVEL EIT MEDIUM UNDER THE INFLUENCE OF AN EXTERNAL MAGNETIC FIELD: AN ANALYTICAL APPROACH - Le Thi Minh Phuong; Dinh Xuan Khoa; Nguyen Huy Bang; Thai Doan Thanh; Nguyen Tuan Anh; Nguyen Thi Thu Hien; Hoang Minh Dong (Tạp chí Khoa học Đại học Đà Lạt)
We investigate the behavior of optical bistability in a degenerate two-level atomic medium using an external magnetic field to separate the lower level into two distinct levels that both connect to an upper level by the probe and coupling laser fields. Based on analytical solutions, the absorption spectrum and behavior of optical bistability in an electromagnetically induced transparency regime under an external magnetic field are investigated. By controlling the external magnetic field, we find that the appearance and disappearance of the optical bistability can be easily controlled according to the strength of the magnetic field in the transparent window domain. Furthermore, the effects of the intensity of the coupling laser field and the parameters of the system on the behavior of optical bistability are also considered. The proposed model is useful for applications in all-optical switches and magneto-optic storage devices.